Efficacy of different allergen-specific immunotherapies for the treatment of allergic rhinitis in children and adults: an umbrella review - He, Yu; Liu, Xinghong; Zhou, Bin; Dai, Tianrong (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study was to summarize the therapeutic efficacy of various allergen immunotherapy (AIT) in the treatment of allergic rhinitis (AR) among different populations and for different allergens.MethodsSystematic reviews or meta-analyses related to the efficacy of AIT in the treatment of AR until October 2024 were retrieved from PubMed, Web of Science, Embase, and Cochrane Library. Each study was independently evaluated by two investigators in accordance with the inclusion and exclusion criteria. The methodological quality was assessed using AMSTAR 2, and the quality of evidence was evaluated by the GRADE system.ResultsA total of 16 SRs/Mas were included. The methodological quality was evaluated by AMSTAR 2, with 5 rated as “low” and the remainder as “very low”. The quality of the evidence was assessed using the GRADE system. It was found that the quality of evidence in most studies was unsatisfactory. Among the included articles, six had moderate-quality evidence, six had low-quality evidence, and four had very low-quality evidence, with no high-quality evidence. There was a moderate degree of overlap among the included literature. After conducting an overall efficacy evaluation of the extracted data, it was found that SLIT, SCIT, and LNIT were effective in the treatment of AR, while cluster SCIT and ILIT had no significant efficacy compared with placebo.ConclusionSLIT and SCIT are active and effective treatments for AR, and show significant efficacy in adults, children, and for different allergens. There are still relatively few meta-analyses and systematic reviews of cluster SCIT, ILIT, and LNIT, and there is still scope for further improvement in the assessment of their efficacy. Considering that the methodological quality and evidence of the systematic reviews and meta-analyses included in this study are generally low, more high-quality, large-scale, multicenter, randomized controlled clinical trials are indispensable in the future to firmly verify the efficacy of various AIT in the treatment of AR in different populations and allergens.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024600378.